1999
DOI: 10.1042/0264-6021:3370543
|View full text |Cite
|
Sign up to set email alerts
|

Glutamine synthesis is heterogeneous and differentially regulated along the rabbit renal proximal tubule

Abstract: Glutamine synthesis, a major process for ammonia detoxification and the control of acid-base balance, occurs from various precursors in suspensions of rabbit proximal tubules. However, no data are currently available on the distribution of glutamine synthesis along the rabbit proximal tubule, and its modulation by changes of substrate concentration. Therefore we have microdissected and incubated the three parts (S1, S2 and S3) of rabbit proximal tubules and measured glutamine synthesis from alanine and asparta… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1999
1999
1999
1999

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…It is known that the rabbit kidney, which produces an alkaline urine [2], contains a high activity of glutamine synthetase [1][2][3] located in the proximal tubule [4] and does not readily use glutamine as substrate [10,27] because its glutaminase activity is low [2]. Accordingly, in the rabbit, the urinary excretion of ammonium ions is low and the high rate of renal glutamine synthesis known to occur in itro [1,[7][8][9][10][11] seems to be an important process that detoxifies the great quantities of ammonia produced by the very active glutamate dehydrogenase reaction in this organ. The rabbit renal proximal tubule also has a high capacity to metabolize acetate [9] (Table 1), the most concentrated volatile fatty acid in the rabbit blood [12].…”
Section: Physiological Significancementioning
confidence: 99%
See 1 more Smart Citation
“…It is known that the rabbit kidney, which produces an alkaline urine [2], contains a high activity of glutamine synthetase [1][2][3] located in the proximal tubule [4] and does not readily use glutamine as substrate [10,27] because its glutaminase activity is low [2]. Accordingly, in the rabbit, the urinary excretion of ammonium ions is low and the high rate of renal glutamine synthesis known to occur in itro [1,[7][8][9][10][11] seems to be an important process that detoxifies the great quantities of ammonia produced by the very active glutamate dehydrogenase reaction in this organ. The rabbit renal proximal tubule also has a high capacity to metabolize acetate [9] (Table 1), the most concentrated volatile fatty acid in the rabbit blood [12].…”
Section: Physiological Significancementioning
confidence: 99%
“…of "$C label from [3-"$C]alanine that entered the tricarboxylic acid cycle via pyruvate carboxylase relative to the proportion that entered via pyruvate dehydrogenase was no different from that obtained in tubules from normal rabbits. We have recently demonstrated that the rate of glutamine synthesis along the proximal tubule from both alanine and aspartate is regulated in a segment-and substrate concentration-dependent manner [11]. Lietz and Bryla [8] and Lietz et al [7] have also studied the influence of glycerol, lactate and ketone bodies, which are potentially important substrates for rabbit proximal tubules, on glutamine synthesis from alanine and aspartate.…”
Section: Introductionmentioning
confidence: 99%